Level and Health Risk Evaluation of Heavy Metals and Microorganisms in Urban Soils of Lagos, Southwest Nigeria - Yahaya, Tajudeen O. (Algerian Journal of Biosciences, 2020)
Heavy metal and microbial pollution of the environment are linked to the increasing prevalence of diseases worldwide. Accordingly, this study assessed the safety of urban soils in Lagos, Nigeria, with regard to the levels of lead (Pb), nickel (Ni), cadmium (Cd), copper (Cu), chromium (Cr), zinc (Zn), and microorganisms. Soil samples were collected from Iwaya, Makoko, and Ilaje areas of the city and subjected to atomic absorption spectroscopy (AAS) and microbiological examinations using standard protocols. The mean values obtained for the heavy metals and microorganisms were compared with the World Health Organization (WHO) permissible limits. The average daily oral ingestion (ADOI), average daily dermal ingestion (ADDI), and the hazard quotient (HQ) of the heavy metals were also calculated. The AAS indicated that the soils in the three areas contained non-permissible levels of the evaluated heavy metals, except Cu and Cd. The microbiological examinations also showed that the soils contained abnormal levels of heterotrophic bacteria (HB), hydrocarbon utilizing bacteria (HUB), heterotrophic fungi (HF), and hydrocarbon utilizing fungi (HUF). The ADOI of the heavy metals in the three areas were above the recommended levels, while ADDI were normal. Moreover, the HQ of oral ingestion of each heavy metal except Cr was greater than one, while the HQ of dermal ingestion of the heavy metals was less than one. These findings suggest that the soils could predispose the residents in the areas to diseases. Thus, there is a need for regular environmental sanitation and environmental pollution control in the areas, and personal hygiene.